2023
DOI: 10.3389/fmicb.2023.1124144
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-MS-MS quantification of short-chain fatty acids actively secreted by probiotic strains

Abstract: IntroductionShort-chain fatty acids (SCFAs) are the main by-products of microbial fermentations occurring in the human intestine and are directly involved in the host’s physiological balance. As impaired gut concentrations of acetic, propionic, and butyric acids are often associated with systemic disorders, the administration of SCFA-producing microorganisms has been suggested as attractive approach to solve symptoms related to SCFA deficiency.MethodsIn this research, nine probiotic strains (Bacillus clausii N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
15

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 62 publications
1
4
0
15
Order By: Relevance
“…Further exploration established a robust correlation between embryonic colon GPR41 expression and maternal cecum propionate levels, suggesting that propionate exerts its development in uence on the ENS through GPR41 signaling pathway. Consistent with previous reports 43,44 , our study also demonstrated that L. reuteri enhances host propionate production. Our intervention with L. reuteri in ABX dams further con rms the pivotal role of the propionate-GPR41-GDNF/RET/SOX10 pathway in ENS development.…”
Section: Discussionsupporting
confidence: 93%
“…Further exploration established a robust correlation between embryonic colon GPR41 expression and maternal cecum propionate levels, suggesting that propionate exerts its development in uence on the ENS through GPR41 signaling pathway. Consistent with previous reports 43,44 , our study also demonstrated that L. reuteri enhances host propionate production. Our intervention with L. reuteri in ABX dams further con rms the pivotal role of the propionate-GPR41-GDNF/RET/SOX10 pathway in ENS development.…”
Section: Discussionsupporting
confidence: 93%
“…Short-chain fatty acids are molecules produced by probiotic S. boulardii which are known to have potent anti-inflammatory effects on the host 65 . To evaluate whether genetic modification and/or the presence of antibodies impact the secretion of commonly measured short-chain fatty acids, we measured the concentration of acetate, propionate, and butyrate in the supernatant of S. boulardii cultures as a function of time, at 6 h, 12 h, and 18 h. Figure 3C, D illustrates that all groups exhibit comparable secretion levels of propionate, with a minor difference (1.1-fold) between the S.b.…”
Section: Resultsmentioning
confidence: 99%
“…Ácido acético: Regulación del metabolismo lipídico y del peso corporal. Las nueve cepas probióticas analizadas fueron capaces de secretar ácido acético [2].…”
Section: Los Probióticos Para Favorecer El Equilibrio Fisiológico Med...unclassified
“…Las cuatro cepas de B. clausii, así como S. boulardii, secretaron ácido propiónico. B. coagulans, B. breve, L. reuteri y L. rhamnosus no secretaban ácido propiónico [2].…”
Section: Los Probióticos Para Favorecer El Equilibrio Fisiológico Med...unclassified
See 1 more Smart Citation